Merajut Batam masa depan : menyongsong status free-trade zone - Muliono, Heri, 1957- (Jakarta : Pustaka LP3ES Indonesia, 2001)
Economic prospects of Batam Island as a free trade zone
Rujukan : p. [243]-253
Keywords: Free ports and zones -- Indonesia; Batam Island (Indonesia) -- Economic condition